2015
DOI: 10.1016/j.cbpb.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Starving/re-feeding processes induce metabolic modifications in thick-lipped grey mullet (Chelon labrosus, Risso 1827)

Abstract: The effects of starvation and re-feeding on metabolites and tissue composition, GH/IGF-I axis, and digestive enzyme activities in juvenile thick-lipped grey mullet (Chelon labrosus) were evaluated. Fish were divided into three feeding groups (n=72, 82.00±4.09 g initial body mass). The control group was fed 1% of their body mass once a day throughout the experiment with commercial pellets. The other two groups were deprived of feed for 21 days (starved), or re-fed for 7 days after 14 days of food deprivation (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
5
22
0
Order By: Relevance
“…Moreover, in other teleost species, a compensatory growth has been associated with a reduction of hepatic IGF-I mRNA levels (Picha et al, 2006), hence this fact observed at day 75 may have been due to increased plasma IGF-I levels as a consequence of its higher mRNA expression, maintaining similar SGR under the three different stocking densities studied. Furthermore, other chronic stress situations as starving produced the typical response of this axis with an increase in pituitary GH mRNA and a decrease in hepatic IGF-I mRNA in C. labrosus (Pujante et al, 2015), suggesting a clear dependence related to the stress source applied.…”
Section: Tablementioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, in other teleost species, a compensatory growth has been associated with a reduction of hepatic IGF-I mRNA levels (Picha et al, 2006), hence this fact observed at day 75 may have been due to increased plasma IGF-I levels as a consequence of its higher mRNA expression, maintaining similar SGR under the three different stocking densities studied. Furthermore, other chronic stress situations as starving produced the typical response of this axis with an increase in pituitary GH mRNA and a decrease in hepatic IGF-I mRNA in C. labrosus (Pujante et al, 2015), suggesting a clear dependence related to the stress source applied.…”
Section: Tablementioning
confidence: 96%
“…The main compounds of the somatotropic axis (i.e., GH and IGF-I) have been recently reported for C. labrosus by Pujante et al (2015). GH, secreted in the adenohypophysis and under hypothalamic control, is involved in the regulation of somatic growth through the induction of IGF-I (Björnsson, 1997;Chen et al, 1994;Pérez-Sánchez, 2000).…”
Section: Tablementioning
confidence: 98%
See 2 more Smart Citations
“…It is well known that the neuroendocrine regulation of GH secretion in fish is multifactorial, with a balance of stimulatory and inhibitory neurohormones acting on pituitary somatotrophs. In addition, temperature (Picha et al, 2009;Zhou et al, 2015), season (Picha et al, 2009;Richmond, Jeanniard du Dot, Rosen, & Zinn, 2010), salinity (Moorman, Yamaguchi, Lerner, Grau, & Seale, 2016), starvation and refeeding (Pujante et al, 2015;Won & Borski, 2013), age (Li, Chen, Wong, & Lin, 2005;Richmond et al, 2010), gender (Ma et al, 2012), hormones (Linan-Cabello, Robles-Basto, & Mena-herrera, 2013;Wu, Li, Lin, & Li, 2012), diets (Li, Liu, Zhang, Ma, & Lin, 2013) and transgenosis (Abernathy et al, 2015;Leggatt et al, 2009;White, Volkoff, & Devlin, 2016) can also affect its distribution in tissues. Li et al (2013) found that cysteamine hydrochloride (CSH) feeding could induce the growth rate in Epinephelus coioides, and the luteinizing hormone-releasing hormone analogue (LHRH-A) could potentiate this growth stimulation effect.…”
Section: Introductionmentioning
confidence: 99%